Hyperbaric therapy of patients poisoned with carbon monoxide in the Hospital Emergency Department at University Hospital No. 1 named after Dr Antoni Jurasz in Bydgoszcz - preliminary report - Ewa Zieliński; Ahmad El-Essa; Kinga Grobelska; Piotr Dzięgielewski; Oksana Telak; Walery Zukow (Kazimierz Wielki University, 2018)
The study is a preliminary report on the treatment of carbon monoxide poisoning at the Hospital Emergency Department at University Hospital No. 1 named after Dr. Antoni Jurasz in Bydgoszcz, with the use of oxybarotherapy in a monoplace chamber. Carbon monoxide (CO) poisoning is a frequent cause of accidental and intentional injuries in the world. Many researchers suggest that the use of hyperbaric oxygen (HBO) in CO poisoning, prevents the development of neurological sequelae. This led to the widespread use of HBO in the treatment of patients with carbon monoxide poisoning. The National Health Fund (NHF) reimburses patients treatment in a multi-person hyperbaric chamber. In the Hospital Emergency Department (HED) in Bydgoszcz there is a one-person hyperbaric chamber, which is mainly used to treat patients poisoned with CO. Treatment is also refunded by the NHF. The cost of treating the patient in the monoplace chamber is included in the contract - (lump sum) from NHF for HED.